2018
DOI: 10.1097/md.0000000000009545
|View full text |Cite
|
Sign up to set email alerts
|

Detection and genotyping of human papillomavirus (HPV) in HIV-infected women and its relationship with HPV/HIV co-infection

Abstract: HPV have been identified as high-risk and low-risk, depending on their association with the development of cancer. HPV infections can be facilitated by co-infection with HIV. Here, we investigated HPV prevalence and genotypes and the risk factors affecting HPV/HIV co-infection. Forty HIV-positive patients had 80 cervical swab samples collected in 2 consecutive years. Polymerase chain reaction and DNA direct sequencing were used to perform HPV genotyping. Statistical analyses were performed regarding risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 38 publications
5
45
0
2
Order By: Relevance
“…The mean age was 37 years ±3 years, similar between HIV-seropositive women (36.7 years) as compared to HIVseronegative women (37.3 years). The most represented age range was [30][31][32][33][34][35][36][37][38][39] years (44%). Single women were the most represented (58.88%), followed by married women (28.97%), widows (9.34%), and divorced (2.80%).…”
Section: Sociodemographic and Bioclinical Characteristics Of The Studmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age was 37 years ±3 years, similar between HIV-seropositive women (36.7 years) as compared to HIVseronegative women (37.3 years). The most represented age range was [30][31][32][33][34][35][36][37][38][39] years (44%). Single women were the most represented (58.88%), followed by married women (28.97%), widows (9.34%), and divorced (2.80%).…”
Section: Sociodemographic and Bioclinical Characteristics Of The Studmentioning
confidence: 99%
“…Several HPV genotypes were identified in the study population. Interestingly, 74% of women were infected by non-discriminated high-risk genotypes (31,33,35,39,45,51,52, 56, 56, 58 and 11 others) as per the genotyping assay. Surprisingly, only 3% and 4% of the study population were infected solely with HPV 16 and HPV 18 respectively (Figure 1).…”
Section: Diversity Of Hpv Genotypes In Infected Womenmentioning
confidence: 99%
“…Tartaglia et al ., in a cross‐sectional study with 200 HIV+ and HIV‐women, showed that overall HPV‐prevalence was 33% with a higher prevalence (48%) in the HIV‐positive group. Badial et al . found that prevalence of HPV, collected in two consecutive years, in 40 HIV‐positive women was 73.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the hrHPV strains co-infection has been shown to increase the death rate of HIV patients. 91 Conserved epitopes provide powerful immunization for prolonged period. Sabah et al 92 found that the single 9mer CTL epitope ETSVHEIEL was conserved (100%) in all E6 proteins of HPV58 isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Among the five epitopes of E6 protein, RTEVYQFAF [41][42][43][44][45][46][47][48][49] and YSRIRE-LRY [72][73][74][75][76][77][78][79][80] were predicted to have binding affinity for HLA-A*(32:01, 29:02) and HLA-B*58: 01 MHC class I alleles (Table 1D). Out of 13 MHC-binding E7 peptides (Table 1E), STLSFVCPW [93][94][95][96][97][98][99][100][101] (HLA-A*32:01, HLA-B*58:01, HLA-B*57:01), LQQLFLSTL [87][88][89][90][91][92][93][94][95] (HLA-A*02:06), and QLFLSTLSF [89][90][91][92][93][94][95][96][97] (HLA-B*15:02, HLA-B*15:01, HLA-A*32:01) were predicted to have a binding affinity of IC 50 <200 nm. Furthermore, three out of seven epitopes of L1 protein, such as HVEEYDLQF…”
Section: Cd8 + Ctl Epitopesmentioning
confidence: 99%